Social innovation concept and implementation in the European Union and in the Republic of Lithuania - Skaidrė Žičkienė; Teodoras Tamošiūnas (Social Welfare: Interdisciplinary Approach)
The aim of the paper is to disclose the importance of social innovation and generalize innovation promotion policy in the European Union, assessing the actual situation in Lithuania. The need for social innovation is inevitable as different social problems touch modern society. Business, governments, non-governmental organizations have distinct roles and encourage social innovation in different ways, but political will and financial possibilities can lead to great changes. The policy of promoting innovation in Lithuania is in line with the provisions of EU documents, however, in the general innovation system context, little attention is paid to social innovation. Following the evaluation of Lithuania’s performance of the research and innovation system, it has been determined that the indicators which were evaluated as weaknesses are primarily related to social problems.